Osteoporosis’s undertreatment in Pakistan - Atiq, Usama; Rafique, Rameen; Atiq, Sami; Tehreem, Eesha (Journal of the Pakistan Medical Association, 2023)
Dear Madam, Osteoporosis results in the weakening of the bones over time; this is a preventable medical condition. Unfortunately, this makes people prone to low-impact fractures. People usually know about this disease after fracturing a bone(1). It is estimated that in Pakistan, 9.9 million people have osteoporosis, and 7.2 million are females. The numbers may rise to 12.01 million by 2050 (2). Things are much worse in a country with an ever-expanding population and a limited health budget; DEXA machines are sparse, which leaves clinicians to rely on heel ultrasound scanning. Above all, the lack of solid guidelines and limited patient compliance create havoc regarding this issue. In Pakistan, this disease prevalence is rising exponentially due to multi-parity, extended life post menopause, low calcium and vitamin D intake, and stagnant lifestyle (3). The Asia-Pacific Consortium on Osteoporosis came into existence in 2019 to reduce osteoporosis prevalence in Asia Pacific. Unfortunately, it too confirmed that local guidelines for osteoporosis treatment are non-existence in this part of the world(4). Primary health centres are the initial places to pick osteoporosis; however, studies indicate primary health care physicians feel it challenging to use FRAX (screening test) as there is no formal training to pick signs of osteoporosis(5). Therefore, the health ministry needs to take this issue seriously and form a national-level committee comprising multiple specialities (orthopaedic surgery, endocrinology, rheumatology, family medicine, primary care, etc.). Drafting local guidelines will also be an effective way to treat this silent undertreated disease. In addition, bisphosphonates should be promoted in the diagnosed patients as it has proven to be the most effective method to curb osteoporosis(6). Arranging seminars on world osteoporosis day (20th October) at educational centres, hospitals and public places will promote early seeking of help in case of osteoporosis. Follow-up in patients with diagnosed osteoporosis is crucial; setting up hotlines for such patients at the national level will help doctors fight poor compliance issues regarding management.